2010
DOI: 10.1186/1532-429x-12-74
|View full text |Cite
|
Sign up to set email alerts
|

Peak oxygen uptake in relation to total heart volume discriminates heart failure patients from healthy volunteers and athletes

Abstract: BackgroundAn early sign of heart failure (HF) is a decreased cardiac reserve or inability to adequately increase cardiac output during exercise. Under normal circumstances maximal cardiac output is closely related to peak oxygen uptake (VO2peak) which has previously been shown to be closely related to total heart volume (THV). Thus, the aim of this study was to derive a VO2peak/THV ratio and to test the hypothesis that this ratio can be used to distinguish patients with HF from healthy volunteers and endurance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Moreover, in doubtful cases, the assessment of peak oxygen uptake, which is consistently increased in relation to total heart volume can also help us to distinguish between physiologic and pathologic LV dilatation. 158 Finally, STE might give additional information in terms of myocardial contraction. However, only few studies are available to date with somewhat diverse results on LV function at rest.…”
Section: Dilated Cardiomyopathymentioning
confidence: 99%
“…Moreover, in doubtful cases, the assessment of peak oxygen uptake, which is consistently increased in relation to total heart volume can also help us to distinguish between physiologic and pathologic LV dilatation. 158 Finally, STE might give additional information in terms of myocardial contraction. However, only few studies are available to date with somewhat diverse results on LV function at rest.…”
Section: Dilated Cardiomyopathymentioning
confidence: 99%
“…Several studies of left and right ventricular volumes in athletes have shown physiological adaptation to training that differs from the pathological remodeling found in diseases such as hypertrophic and dilated cardiomyopathies (1)(2)(3)(4)(5). Furthermore, total heart volume (THV) has been shown to increase with long term endurance training, and there is a strong correlation between THV and peak oxygen uptake (VO 2 peak) (4).…”
Section: Introductionmentioning
confidence: 99%
“…Data from the SHOCK trial registry demonstrated that, at inclusion, a low cardiac power output <0.53 W accurately predicted in-hospital mortality [5]. As expected, the mean value of CPI was extremely low at inclusion in cardiogenic shock (0.22 ± 0.08 W/m 2    versus   0.62 ± 0.08 W/m 2 in healthy subjects) while elevated in initial septic shock (0.8 ± 0.13 W/m 2 ) [12, 13]. …”
Section: Discussionmentioning
confidence: 83%